Influence of reflected waves at the bonded boundary in double-layered thickness-shear resonator using α-quartz. (1st July 2022) - Noguchi, Taisei; Ohashi, Yuji; Omote, Masaya; Yokota, Yuui; Kurosawa, Shunsuke; Kamada, Kei; Sato, Hiroki; Toyoda, Satoshi; Yoshino, Masao; Yamaji, Akihiro; Yoshikawa, Akira
Abstract: The influence of the reflected waves at the bonding boundary on the resonance waveform and temperature characteristics was investigated using α -quartz (QZ). The double-layered resonator specimen was fabricated using 129.55° Y - and 0° Y -cut QZ substrates with the thickness ratio x = 0.520. The temperature characteristic of the 1st and 2nd resonance modes at the range from 100 °C to 300 °C was deviated from the calculated values estimated by the equations considering thickness ratio and electric flux density ratio proposed in the previous work. Considering the phase matching conditions, it was clarified that the reflected waves at the bonding boundary are in phase in the lower acoustic impedance substrate and out of phase in the other substrate for the 1st mode, so the temperature characteristics are mainly dominated by that of the lower acoustic impedance substrate. In contrast, these relationships are reversed for the 2nd mode.